Understanding gender inequities in antimicrobial resistance: role of biology, behaviour and gender norms - Esmita Charani; Srishti Goel; Deepshikha Batheja (BMJ Global Health)
Antimicrobial resistance (AMR) poses a critical public health threat, with gendered implications that are often overlooked. Key drivers of bacterial AMR include the misuse of antibiotics, inadequate water, sanitation and hygiene infrastructure and poor infection control practices. Persistent gender discrimination exacerbates these issues, resulting in disparities in healthcare access and outcomes. This review explores how biological, sociocultural and behavioural factors contribute to the differential incidence of AMR in women. We present a conceptual framework to understand how gender norms influence antibiotic use and AMR. Differences in infection susceptibility, health-seeking behaviours, the ability to access and afford essential antibiotics and quality healthcare and appropriate diagnosis and management by healthcare providers across genders highlight the necessity for gender-sensitive approaches. Addressing gender dynamics within the health workforce and fostering inclusive policies is crucial for effectively mitigating AMR. Integrating intersectional and life course approaches into AMR mitigation strategies is essential to manage the changing health needs of women and other vulnerable groups.